Prosthesis and reformation: the Black Rubric and the reinvention of kneeling. Issue 7 (9th November 2016) - Davis, Isabel
ABSTRACT: This essay considers the Black Rubric, a last minute clarification on kneeling at the sacrament of communion inserted into the second edition of the Book of Common Prayer in 1552, as a textual prosthesis, in the terms laid out by David Wills in his book, Prosthesis . This essay uses Wills' thesis to emphasise the material format of the Black Rubric as a textual object more than has been the case in prior scholarship. However, at the same time, this article finds that the example of the Black Rubric modifies and adds intricacy to Wills' account of the Reformation as a process of prostheticisation, breaking up and renovating arrangements inherited from the medieval past. In particular, the Black Rubric forces a qualification of Wills' conclusion about the degree to which print technologies created a distance between text and the human body and foregrounds, more than Wills does, the process of authorising Protestantism as a religion of the state.